Highly Efficient Heavy Atom Free Room Temperature Phosphorescence by Host-Guest Doping - Cao, Jinzhu; Zhang, Meng; Singh, Manjeet; An, Zhongfu; Ji, Lingfei; Shi, Huifang; Jiang, Yijian (Frontiers in Chemistry, 2021)
Recently, there has been remarkable progress of the host-guest doped pure organic room-temperature phosphorescence (RTP) materials. However, it remains a great challenge to develop highly efficient host-guest doping systems. In this study, we have successfully developed a heavy atom free pure organic molecular doped system (benzophenone-thianthrene, respectively) with efficient RTP through a simple host-guest doping strategy. Furthermore, by optimizing the doping ratios, the host-guest material with a molar ratio of 100:1 presented an efficient RTP emission with 46% quantum efficiency and a long lifetime of up to 9.17 ms under ambient conditions. This work will provide an effective way to design new organic doping systems with RTP.